Transformation of game matrix and game value - Vilkas, E. (Lithuanian Mathematical Journal, 1964)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:Э. И. Вилкас. Преобразования матрицы игры и значения игрыE. Vilkas. Lošimo matricos ir lošimo reikšmės transformacijos